Penerapan Model Project Based Learning Dalam Pembelajaraan Menulis Poster Di Kelas VIII SMP 19 Kota Jambi - Anggraini, Dwi Dini; D, Yusra; Rasdawita, Rasdawita (Jurnal Ilmiah Dikdaya, 2024)
This research aims to describe the application of the Project Based Learning model in learning to write posters for class VIIII students. The approach used in this research is qualitative Approach, descriptive research type. Research data in the form of words, phrases, sentences,and a paragraph explaining the application of the Project Based Learning model. Data source for This research is a teaching module for Indonesian language teachers in class VIII. The results of this research show that is the application of the Project Based Learning model in learning to write posters for class VIII students, in the steps of determining a project, designing a project plan, preparing a schedule, and monitoring the progress of student projects, carried out in accordance with the Project syntax Based Learning Model. However, at the trial stage the project results have not yet been carried out optimally due to time constraints, so teachers assess based on student project results only. Based on the research results, it can be concluded that the implementation of Project Based Learning The overall poster writing model for class VIII students is implemented according to the steps Project Based Learning model designed in teaching modules.